Production method of flame retardant polyester fiber products

By performing flame retardant treatment and alcoholylation treatment of phosphorus-containing compounds after spinning the polyester fiber, combined with the ratio optimization of high melt index polyester and low melt index PET, the problem of degradation of flame retardant performance of polyester fibers is solved, and high flame retardant performance and good mechanical properties are achieved.

CN116463853BActive Publication Date: 2025-03-25SHANGHAI YINGFAN CHEM NEW MATERIAL CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211565024.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-07
Publication Date
2025-03-25
Estimated Expiration
2042-12-07

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the chemical activity of the fiber surface while improving the flame retardant properties and mechanical properties of polyester fibers, resulting in a decrease in the flame retardant properties during use.

Method used

After spinning the polyester melt, the flame retardant treatment is performed using a phosphorus-containing compound, combined with alcoholylation treatment to improve the chemical activity of the fibers, and the flame retardant performance of the fibers is improved by optimizing the proportion of a specific high melt index polyester to a low melt index PET.

Benefits of technology

The high flame retardant performance and good mechanical properties of polyester fiber are achieved. After the fiber surface is activated, the flame retardant effect can be maintained for a longer time, and the limit oxygen index is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116463853B_ABST
    Figure CN116463853B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for producing a flame-retardant polyester fiber product, which has the characteristics of good fiber mechanical properties and good flame retardant properties. The technical scheme is: the method for producing a flame-retardant polyester fiber product comprises the following steps: (1) a polyester melt is subjected to spinning, drawing, and shaping to obtain a primary polyester fiber; (2) in the presence of an esterification reaction catalyst, the primary fiber product is subjected to flame retardant treatment using a phosphorus-containing compound containing the following structural fragments, wherein the polyester in step (1) comprises a low melt index PET and a high melt index polyester:
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a production method of flame-retardant polyester fiber products, in particular to a production method of flame-retardant fibers or flame-retardant fabrics. Background Art

[0002] Polyester fiber is a basic raw material for textiles. With its comprehensive cost-effectiveness, it is widely used in clothing, home furnishings and industrial textiles. In 2021, the global polyester fiber production reached 60 million tons, ranking first among all fiber varieties. With the continuous upgrading of terminal consumer demand, the performance requirements of polyester fiber products are getting higher and higher, and the functionalization of polyester fiber has become more and more urgent. Conventional polyester fiber has good mechanical properties and wear resistance, but its hygroscopicity is poor when used as a clothing fiber material, and the moisture regain under standard conditions is only 0.4%; when used as industrial paper reinforcement, it is often difficult to disperse evenly, resulting in poor reinforcement effect. In order to improve these shortcomings of polyester fiber, modification is necessary. In view of the above shortcomings, the essence is that polyester fiber lacks reactive functional groups, especially the chemical properties of the fiber surface are inert, resulting in low moisture absorption and difficulty in fiber surface modification. How to achieve surface activation of polyester fiber materials and enhance their ability to be further applied or react is an important direction for improving the functionalization of polyester fibers.

[0003] Chinese invention patent CN110528109B discloses a high-strength flame-retardant polyester industrial yarn and a preparation method thereof. The method comprises preparing phosphorus-containing thickened polyester chips by utilizing low-temperature vacuum thickening, high-temperature vacuum thickening and high-temperature solid phase thickening processes, and preparing the high-strength flame-retardant polyester industrial yarn by utilizing the flame-retardant thickened polyester chips melt spinning process.

[0004] Chinese invention patent CN102102241A discloses a production method for directly manufacturing flame-retardant polyester staple fibers from recycled polyester bottle flakes, wherein the dried polyester bottle flakes and flame-retardant polyester masterbatch are mixed and spun to prepare flame-retardant polyester staple fibers.

[0005] Chinese invention patent CN112195532A discloses a flame-retardant polyester master yarn and its preparation process, which adopts the steps of melt blending of a flame-retardant blending agent and polyester fiber masterbatch, extruding and spinning to obtain spun fibers, and then post-finishing the spun fibers with phosphate ester and penetrant to obtain the flame-retardant polyester master yarn.

[0006] From the existing technology, polyester fibers achieve flame retardancy mainly by introducing flame retardants for copolymerization during the polyester synthesis stage, introducing masterbatches containing flame retardants during the polyester melt spinning stage, or flame retardant treatment of the fibers. Among them, the copolymerization or blending method will have a great impact on the mechanical properties of the prepared flame retardant polyester fibers, especially the copolymerization method, which destroys the original molecular chain regularity of polyester. Although the fiber material post-treatment method is highly efficient, the surface of polyester fibers is chemically inert and it is difficult to achieve chemical grafting. It is mostly attached to the fiber surface by physical bonding force, is not resistant to washing, and the flame retardancy decreases significantly during use. Summary of the invention

[0007] One of the technical problems to be solved by the present invention is to provide a new method for producing flame-retardant polyester fiber products, which has the characteristics of good fiber mechanical properties and good flame retardant properties.

[0008] In order to solve one of the above technical problems, the technical solution adopted by the present invention is as follows:

[0009] The production method of flame retardant polyester fiber products comprises the following steps:

[0010] (1) The polyester melt is subjected to spinning, drawing and shaping to obtain primary polyester fiber;

[0011] (2) In the presence of an esterification reaction catalyst, the primary fiber product as the object to be flame retardant treated is flame retardant treated with a phosphorus-containing compound containing the following structural fragments:

[0012]

[0013] The polyester in step (1) includes low melt index PET (PET is the abbreviation of polyethylene terephthalate) and high melt index polyester.

[0014] In the above technical solution, the primary fiber product is the primary polyester fiber in step (1) or a fabric made from the primary polyester fiber in step (1), and the fabric is preferably knitted or woven.

[0015] In the above technical solution, the melt index (280°C / 2.16kg) of the low melt index is preferably a g / 10min, and a is 10 to 30. For example, but not limited to, a is 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, etc. For comparison only, the low melt index used in the specific embodiment of the present invention is provided by Sinopec Yizheng Chemical Fiber Co., Ltd., with a grade of FD501, a marked melt index of 24 to 26 g / 10min (280°C / 2.16kg), and a measured melt index of 25.7 g / 10min (280°C / 2.16kg).

[0016] In the above technical solution, the melt index (280°C / 2.16kg) of the high melt index polyester is preferably b g / 10min, b=a+c, c is greater than 0 and less than 90. For example, but not limited to, c is 5, 10, 15, 20, 25, 33, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, etc. More preferably, c is 30-60.

[0017] In the above technical solution, the high melt index polyester preferably includes at least one selected from the group consisting of high melt index PET (PET is the abbreviation of polyethylene terephthalate), high melt index PTT (PTT is the abbreviation of poly(1,3-propylene terephthalate) and high melt index PBT (PBT is the abbreviation of poly(1,4-butylene terephthalate).

[0018] We surprisingly found that, because the polyester in step (1) includes low melt index PET and high melt index polyester, the limiting oxygen index of the flame retardant fiber product is improved compared with the step of spinning PET with low melt index alone. In particular, when the high melt index polyester is PTT or PBT, the low melt index PET and the high melt index polyester have a significant mutual promotion effect in improving the limiting oxygen index of the flame retardant fiber product.

[0019] When the high melt index polyester includes both high melt index PBT and high melt index PTT, the high melt index PBT and the high melt index PTT have a significant synergistic effect on improving the limiting oxygen index of the flame retardant fiber product.

[0020] When the high melt index polyester includes both high melt index PBT and high melt index PTT, there is no other limitation on the ratio between the high melt index PBT and the high melt index PTT, and comparable mutual synergy can be achieved. As a non-limiting example only, the mass ratio between the high melt index PBT and the high melt index PTT is 0.1 to 10, such as but not limited to 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, etc. As an example only, in the embodiment in which high melt index PBT and high melt index PTT are used at the same time, the mass ratio between the high melt index PBT and the high melt index PTT is 1.

[0021] In a specific embodiment of the present invention, the high melt index PET is produced by Sinopec Yizheng Chemical Fiber Co., Ltd., with a brand name of HS550, a marked melt index (280°C / 2.16kg) of 71-73 g / 10min, and a measured melt index (280°C / 2.16kg) of 71.3 g / 10min.

[0022] In a specific embodiment of the present invention, the high melt index PTT is produced by Zhangjiagang Meijingrong Chemical Industry Co., Ltd., with a brand name of MJR101, a marked melt index (280°C / 2.16kg) of 71-74 g / 10min, and a measured melt index (280°C / 2.16kg) of 72.7.

[0023] In a specific embodiment of the present invention, the high melt index PBT is produced by Zhejiang Meiyuan New Materials Co., Ltd., with a brand name of MY10, a marked melt index (280°C / 2.16kg) of 72-75 g / 10min, and a measured melt index (280°C / 2.16kg) of 72.1 g / 10min.

[0024] In the above technical solution, the mass ratio of the high melt index polyester to the low melt index PET is preferably greater than 0 and less than 0.2. For example, but not limited to, the mass ratio is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, etc., more preferably 0.01 to 0.15. For comparison only, the mass ratio of the high melt index polyester to the low melt index PET in the embodiment of the present invention is 0.05.

[0025] In the above technical solution, the preferred spinning temperature is preferably 260-295° C., for example but not limited to 265° C., 270° C., 275° C., 280° C., 285° C., 290° C. For comparison only, the spinning temperature in the embodiments of the present invention and the comparative examples is 285° C.

[0026] In the above technical solution, the drafting ratio is preferably 3.0-5.0, for example but not limited to 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, etc. For comparison only, the drafting ratio of the fiber in the embodiment and the comparison is 4.0.

[0027] In the above technical solution, the drafting temperature is preferably 60-80°C, for example, but not limited to, the drafting temperature is 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, etc. For comparison only, the drafting temperature of the fiber in the embodiment and the comparison is 65°C.

[0028] In the above technical scheme, the preferred setting temperature is 140 to 160°C, for example but not limited to the setting temperature is 141°C, 142°C, 143°C, 144°C, 145°C, 146°C, 147°C, 148°C, 149°C, 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C, etc. For comparison only, the setting temperature of the embodiment and the comparison is 150°C.

[0029] In the above technical solution, preferably and for the sake of comparison, the phosphorus-containing compound described in step (2) includes cyclohexanehexol hexaphosphate.

[0030] In the above technical scheme, the preferred esterification catalyst is a compound having a sulfonic acid group, such as but not limited to methanesulfonic acid, benzenesulfonic acid, and p-toluenesulfonic acid. For comparison only, the esterification catalysts used in the embodiments of the present invention are all methanesulfonic acid.

[0031] In the above technical solution, the flame retardant treatment described in step (2) preferably comprises the following steps:

[0032] (i) impregnating the object to be flame retardant treated with a flame retardant treatment liquid to obtain an object to be dried, wherein the flame retardant treatment liquid contains the above-mentioned phosphorus-containing compound and an esterification reaction catalyst;

[0033] (ii) Drying.

[0034] In the above technical solution, preferably, the solvent of the flame retardant treatment liquid in step (i) is water.

[0035] In the above technical scheme, the weight content of the phosphorus-containing compound in the flame retardant treatment liquid of step (i) is preferably 10-40%. For example, but not limited to, the weight content of the phosphorus-containing compound in the flame retardant treatment liquid is 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, etc. For comparison only, the weight content of the phosphorus-containing compound in the flame retardant treatment liquid used in the embodiments and comparative examples is 30%.

[0036] In the above technical solution, the immersion time of step (i) is preferably 10 to 90 min, for example but not limited to 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min and the like.

[0037] In the above technical scheme, there is no special requirement for the temperature of the impregnation in step (i), and those skilled in the art can reasonably choose it, and can achieve comparable technical effects without creative work. For example, but not limited to, the impregnation temperature is 5 to 50°C, and more specific examples of the impregnation temperature can be 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, etc. For the convenience of comparison, in the specific embodiments and comparative examples of the present invention, the impregnation temperature in step (i) is 25°C.

[0038] In the above technical solution, the mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid in step (i) is preferably 0.01 to 0.1. For example but not limited to 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, etc. For the convenience of comparison, in the specific embodiments and comparative examples of the present invention, the mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.05.

[0039] In the above technical scheme, the liquid holding capacity of the flame retardant treatment liquid of the object to be dried in step (i) is preferably 10-30% by weight. It is understood by those skilled in the art that, here, the liquid holding capacity of the flame retardant treatment liquid of the object to be dried is based on weight and relative to the object to be flame retardant. It is known to those skilled in the art that the liquid holding capacity can be controlled according to the ability of the object to be flame retardant to absorb the flame retardant treatment liquid, and whether it is squeezed after impregnation and the degree of squeezing. As a non-limiting example, the liquid holding capacity of the flame retardant treatment liquid of the object to be dried in step (i) is, for example but not limited to, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, etc. Only for comparison, the liquid holding capacity of the flame retardant treatment liquid in the embodiments of the present invention and the comparative examples is controlled to be 20%.

[0040] In the above technical scheme, the amount of the esterification catalyst used is preferably 100 to 1000 ppm by weight relative to the phosphorus-containing compound, for example but not limited to 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 550 ppm, 600 ppm, 650 ppm, 700 ppm, 750 ppm, 800 ppm, 850 ppm, 900 ppm, 950 ppm, etc. For comparison only, in the examples of the present invention and the comparative examples, the amount of the esterification catalyst used is 200 ppm by weight relative to the phosphorus-containing compound.

[0041] In the above technical solution, the drying temperature of step (ii) is preferably 120-180° C. For example, but not limited to, the drying temperature is 125° C., 130° C., 135° C., 140° C., 145° C., 150° C., 155° C., 160° C., 165° C., 170° C., 175° C., etc. For comparison only, the drying temperature of step (ii) in the embodiment of the present invention and the comparative example is 150° C.

[0042] In the above technical scheme, the drying time of step (ii) is preferably 3 to 15 minutes, for example but not limited to 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, etc. In the drying process of step (ii), the removal of water promotes the reaction between the hydroxyl groups on the surface of the object to be treated and the flame retardant groups, and realizes the chemical bonding between the object to be treated and the flame retardant species. For comparison only, the drying time of step (ii) in the embodiment of the present invention and the comparative example is 10 minutes.

[0043] In the above technical scheme, preferably, the primary fiber product comprises a material to be alcoholyzed which is obtained by subjecting the material to surface alcoholyzation treatment with an alcohol hydroxyl compound, and the material to be alcoholyzed is the primary polyester fiber of step (1) or a fabric made of the primary polyester fiber of step (1), and preferably the fabric is knitted or woven.

[0044] In the above technical solution, the alcoholic hydroxyl functionality of the alcoholic hydroxyl-containing compound is greater than 2. The primary polyester fiber of step (1) or the fabric made of the primary polyester fiber of step (1) is first subjected to surface alcoholysis treatment and then subjected to flame retardant treatment of step (2), and the obtained fabric product has better flame retardant effect and higher limiting oxygen index.

[0045] In the above technical scheme, as a non-limiting example, for example but not limited to, the alcoholic hydroxyl compound includes at least one selected from the group consisting of substances with alcoholic hydroxyl functionality of 2, 3, 4, 5, 6, 7, 8, 9 and 10, or the average functionality of the alcoholic hydroxyl compound is 2 to 10. Preferably, the alcoholic hydroxyl group in the alcoholic hydroxyl compound is a primary alcohol hydroxyl group. As a non-limiting example, the specific compound can be ethylene glycol, propylene glycol, butanediol or pentanediol, glycerol, trimethylolpropane, pentaerythritol, sorbitol, mannitol, etc., or a mixture thereof, preferably including a hydroxyl-containing compound with a hydroxyl functionality greater than 3. Those skilled in the art know that when pentaerythritol is used, since pentaerythritol has a very high melting point, it is preferably used in the form of a pentaerythritol-ethylene glycol mixture dissolved in ethylene glycol. Only for comparison, the alcoholic hydroxyl compound with an alcoholic hydroxyl functionality greater than 2 used in the embodiment of the present invention is represented by trimethylolpropane, and the alcoholic hydroxyl compound with an alcoholic hydroxyl functionality of 2 is represented by ethylene glycol.

[0046] We found that the greater the alcohol hydroxyl functionality of the alcohol hydroxyl-containing compound, the better the flame retardant effect of the fabric product. For example, compared with the same period last year, the alcohol hydroxyl-containing compound with an alcohol hydroxyl functionality of 3 is better than the alcohol hydroxyl-containing compound with an alcohol hydroxyl functionality of 2.

[0047] In the above technical scheme, the alcoholysis temperature is preferably 150-200°C, for example but not limited to 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, etc. For comparison only, the alcoholysis temperature in the embodiments of the present invention and the comparative examples is 190°C.

[0048] In the above technical scheme, the alcoholysis time is preferably 10 to 100 seconds, such as but not limited to 15 seconds, 20 seconds, 25 seconds, 30 seconds, 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, 60 seconds, 65 seconds, 70 seconds, 75 seconds, 80 seconds, 85 seconds, 90 seconds, 95 seconds, etc. For comparison only, the alcoholysis time in the embodiments of the present invention and the comparative examples is 50 seconds.

[0049] In the above technical scheme, the mass ratio of the material to be hydrolyzed to the hydroxyl-containing compound is preferably 0.02 to 0.2, for example, but not limited to, the mass ratio of the material to be hydrolyzed to the hydroxyl-containing compound is 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19 and the like.

[0050] In the above technical solution, the alcoholysis process is preferably carried out in the presence of an alcoholysis catalyst.

[0051] In the above technical scheme, the preferred amount of alcoholysis catalyst is equivalent to 50 to 500 ppm by weight of the hydroxyl-containing compound, for example but not limited to 60 ppm, 70 ppm, 80 ppm, 90 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm and the like.

[0052] In the above technical scheme, there is no special restriction on the alcoholysis catalyst, and those skilled in the art can reasonably select commonly used alcoholysis catalysts (for example, alkaline substances, acidic substances, ionic liquids, etc. can be used as alcoholysis catalysts), which can achieve comparable technical effects without creative labor.

[0053] As non-limiting examples of alcoholysis catalysts, for example, alkaline substances (which may be alkaline compounds or solid bases loaded with alkaline compounds) can be used as alcoholysis catalysts, and alkaline compounds include but are not limited to alkali metal hydroxides, alkali metal carbonates, alkali metal bicarbonates, alkali metal acetates, etc. More specific non-limiting examples of alcoholysis catalysts are sodium hydroxide, potassium hydroxide, lithium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, lithium hydroxide, sodium acetate, potassium acetate, and lithium acetate; solid bases loaded with alkaline compounds include but are not limited to magnesium oxide composite silica nanospheres, zinc oxide composite silica nanospheres, and the like.

[0054] As a non-limiting example of an alcoholysis catalyst, for example, an acidic compound (protonic acid or non-protonic acid Lewis acid) can be used as an alcoholysis catalyst. For example, the protonic acid can be, but is not limited to, benzenesulfonic acid, p-toluenesulfonic acid, methanesulfonic acid, solid acid (such as molecular sieve); a metal salt in which a metal (such as, but not limited to, lithium, magnesium, calcium, transition metals in the periodic table) ion can act as a Lewis acid, and a non-limiting example of a metal salt can be a carboxylate (carboxylates are more commonly acetates), chlorides, sulfates, and the like. For example, but not limited to, lithium chloride, magnesium chloride, zinc acetate, manganese acetate, lead acetate, zinc chloride, and the like.

[0055] As a non-limiting example of an alcoholysis catalyst, for example, an ionic liquid can also be used as an alcoholysis catalyst. Specific non-limiting examples of ionic liquids as alcoholysis catalysts are: [bmin]Cl, [bmin]OH, [bmin]ZnCl 3 etc.

[0056] For comparison only, the alcoholysis catalyst used in the specific embodiments of the present invention is zinc acetate.

[0057] Only as non-limiting example, alcoholysis is carried out in alcoholysis tank, alcoholysis tank is filled with hydroxyl-containing compound and required amount of catalyst, the temperature of alcoholysis tank is maintained to be alcoholysis temperature, the material to be alcoholysis is immersed in alcoholysis tank, and impregnated for required time. In order to terminate alcoholysis reaction, cooling can be rapidly performed. A convenient way to terminate alcoholysis reaction is to wash the fiber product with required alcoholysis time from alcoholysis tank immersion time with water, and washing with water can not only reach the purpose of terminating alcoholysis, but also reduce the residual hydroxyl-containing compound of flame retardant treatment material and bring it into subsequent flame retardant treatment solution. Whether washing with water is continuous or intermittent is not particularly limited. When the washing is intermittent, the number of washings is not particularly limited, such as 1 to 5 times (further non-limiting examples are 2 times, 3 times, 4 times, etc.); the amount of water is not particularly limited, for example, but not limited to, the amount of water is 5 to 20 times the weight of the fiber product (more specifically, non-limiting examples are 6 times, 7 times, 8 times, 9 times, 10 times, 11 times, 12 times, 13 times, 14 times, 15 times, 16 times, 17 times, 18 times, 19 times, etc.), and the washing temperature is not particularly limited, such as 0 ~90℃, for example but not limited to 5℃, 10℃, 15℃, 20℃, 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃ and the like; there is no particular limitation on the washing time, for example, the washing time for each time is 5 to 60 minutes, and further examples of the washing time are 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes and the like. After washing, the fiber products are preferably dried to remove the moisture remaining on the fabric, so as to prevent the water on the fiber products from being brought into the flame retardant treatment liquid and causing dilution of the flame retardant treatment liquid. There is no particular restriction on the drying temperature, for example but not limited to a drying temperature of 60 to 200°C, and further non-limiting examples of drying temperatures are 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, etc.; there is no particular restriction on the drying time, for example but not limited to 0.5 hour, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, etc. For comparison only, the fibers were washed twice with water, the amount of water used each time was 10 times the weight of the fiber product, the washing temperature was 50°C, the washing time each time was 30 minutes, and the fibers were dried at 70°C for 4 hours after washing.

[0058] It is known to those skilled in the art that in the above technical solution, the primary fiber product of step (2) can achieve comparable technical effects regardless of whether it is in the form of fiber or fabric, regardless of whether the fiber is long fiber or short fiber, and regardless of whether the fabric is knitted or woven. For comparison only, the fabrics in the embodiments and comparative examples are all made in the most common way, from short fibers to yarns, and then from the yarns to grey fabrics as representatives of primary fiber products.

[0059] The melt index (280°C / 2.16kg) mentioned in the specific embodiments of the present invention complies with the provisions of GB / T 3682.1-2018. The content in brackets following the melt index expression refers to the measurement under the conditions of a temperature of 280°C and a load of 2.16kg.

[0060] In the embodiments of the present invention and the comparative examples:

[0061] 1. The mechanical properties of fabrics are determined by using the standard GB / T 3923.1-2013 to determine the dry breaking strength and elongation of the fabric.

[0062] 2. Limiting Oxygen Index (LOI) Test

[0063] (1) Preparation of fabric to be tested by LOI

[0064] According to GB / T 8629-2017 Domestic Washing and Drying Procedure for Textile Testing, the fabric products obtained in the embodiments of the present invention and the comparative examples were washed and dried for 30 times to obtain the LOI fabric to be tested.

[0065] Washing: The washing machine shall be a) horizontal drum, front-loading washing machine in Section 1.2 of the standard document and type A2 as specified in Table A.1 in Appendix A; Washing materials: Type III, 100% polyester fiber, as specified in Table H.1 in Appendix H of the standard document; Detergent: Select standard detergent 2 as specified in Section 6.1.2 of the standard document; The washing program shall adopt the program specified in program number 4N as specified in Table B.1 in Appendix B of the standard document.

[0066] Drying: Select F-tumble drying in Section 1.4 of the standard document. The tumble dryer should be A2 type tumble dryer specified in Section 5.2.2 of the standard document; the humidity setting of the tumble dryer should refer to Table 2 Tumble Drying Procedure 2 in Section 10.2.4 of the standard document.

[0067] (2) The LOI of the tested fabric is obtained according to the test step (1) of the standard "GB / T 5454-1997 Textile Combustion Performance Test Oxygen Index Method". The higher the LOI, the more difficult the material is to burn, or the better the flame retardant performance.

[0068] The present invention is described in detail below through specific implementation modes and examples. DETAILED DESCRIPTION

[0069] [Comparative Example 1]

[0070] 1. Preparation of primary fiber products

[0071] Preparation of 1.1, 2.22dtex polyester fiber

[0072] The spinning raw material polyester is low melt index PET.

[0073] Low melt index PET chips are melted in a single screw extruder to obtain a melt, and the melt is spun through a spinneret at 285° C. The filaments are drawn at 65° C. with a drawing ratio of 4.0, and are shaped at 150° C. The filaments are cut into 38 mm polyester staple fibers.

[0074] 1.2. Weaving of grey cloth

[0075] The polyester staple fiber of step 1.1 is spun into a 32S / 2 double-ply yarn, and then the double-ply yarn is woven into a yarn with a warp density of 170 strands / 10 cm, a weft density of 126 strands / 10 cm, a width of 160 cm, and a gram weight of 125 g / m 2 Grey cloth.

[0076] 2. Flame retardant treatment

[0077] (i) The grey cloth described in step 1.2 is immersed in a flame retardant treatment liquid for 30 minutes as the object to be flame retardant treated. The immersion temperature is 25°C. The mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.05. The flame retardant treatment liquid is a mixed aqueous solution of methanesulfonic acid and cyclohexanehexol hexaphosphate. The weight content of cyclohexanehexol hexaphosphate in the mixed aqueous solution is 30%, and the weight of methanesulfonic acid is 200 ppmw relative to the weight of cyclohexanehexol hexaphosphate.

[0078] Then the impregnated fiber product is squeezed to obtain the object to be dried (the squeezing times and force are adjusted to control the liquid holding amount of the flame retardant treatment liquid in the object to be dried to be 20%).

[0079] (ii) drying the above-mentioned material to be dried at 150° C. for 10 min to obtain a textile product.

[0080] According to the measurement, the LOI of the fabric product is 21.2%, the breaking strength of the fabric product is 410.1N, and the breaking elongation of the fabric product is 30.3%.

[0081] [Comparative Example 2]

[0082] 1. Preparation of primary fiber products

[0083] Preparation of 1.1, 2.22dtex polyester fiber

[0084] The spinning raw material polyester is high melt index PET.

[0085] The high melt index PET chips are melted in a single screw extruder to obtain a melt, and the melt is spun through a spinneret at 285° C. The filaments are drawn at 65° C. with a drawing ratio of 4.0, and are shaped at 150° C. The filaments are cut into 38 mm polyester staple fibers.

[0086] 1.2. Weaving of grey cloth

[0087] The polyester staple fiber of step 1.1 is spun into a 32S / 2 double-ply yarn, and then the double-ply yarn is woven into a yarn with a warp density of 170 strands / 10 cm, a weft density of 126 strands / 10 cm, a width of 160 cm, and a gram weight of 125 g / m 2 Grey cloth.

[0088] 2. Flame retardant treatment

[0089] (i) The grey cloth described in step 1.2 is immersed in a flame retardant treatment liquid for 30 minutes as the object to be flame retardant treated. The immersion temperature is 25°C. The mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.05. The flame retardant treatment liquid is a mixed aqueous solution of methanesulfonic acid and cyclohexanehexol hexaphosphate. The weight content of cyclohexanehexol hexaphosphate in the mixed aqueous solution is 30%, and the weight of methanesulfonic acid is 200 ppmw relative to the weight of cyclohexanehexol hexaphosphate.

[0090] Then the impregnated fiber product is squeezed to obtain the object to be dried (the squeezing times and force are adjusted to control the liquid holding amount of the flame retardant treatment liquid in the object to be dried to be 20%).

[0091] (ii) drying the above-mentioned material to be dried at 150° C. for 10 min to obtain a textile product.

[0092] According to the measurement, the LOI of the fabric product is 21.6%, the breaking strength of the fabric product is 414.3N, and the breaking elongation of the fabric product is 32.2%.

[0093] [Comparative Example 3]

[0094] 1. Preparation of primary fiber products

[0095] Preparation of 1.1, 2.22dtex polyester fiber

[0096] The spinning raw material polyester is high melt index PTT.

[0097] The high melt index PTT chips are melted in a single screw extruder to obtain a melt, and the melt is spun through a spinneret at 285° C. The filaments are drawn at 65° C. with a drawing ratio of 4.0, and are shaped at 150° C. The filaments are cut into 38 mm polyester staple fibers.

[0098] 1.2. Weaving of grey cloth

[0099] The polyester staple fiber of step 1.1 is spun into a 32S / 2 double-ply yarn, and then the double-ply yarn is woven into a yarn with a warp density of 170 strands / 10 cm, a weft density of 126 strands / 10 cm, a width of 160 cm, and a gram weight of 125 g / m 2 Grey cloth.

[0100] 2. Flame retardant treatment

[0101] (i) The grey cloth described in step 1.2 is immersed in a flame retardant treatment liquid for 30 minutes as the object to be flame retardant treated. The immersion temperature is 25°C. The mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.05. The flame retardant treatment liquid is a mixed aqueous solution of methanesulfonic acid and cyclohexanehexol hexaphosphate. The weight content of cyclohexanehexol hexaphosphate in the mixed aqueous solution is 30%, and the weight of methanesulfonic acid is 200 ppmw relative to the weight of cyclohexanehexol hexaphosphate.

[0102] Then the impregnated fiber product is squeezed to obtain the object to be dried (the squeezing times and force are adjusted to control the liquid holding amount of the flame retardant treatment liquid in the object to be dried to be 20%).

[0103] (ii) drying the above-mentioned material to be dried at 150° C. for 10 min to obtain a textile product.

[0104] According to the measurement, the LOI of the fabric product is 22.1%, the breaking strength of the fabric product is 416.6N, and the breaking elongation of the fabric product is 31.0%.

[0105] [Comparative Example 4]

[0106] 1. Preparation of primary fiber products

[0107] Preparation of 1.1, 2.22dtex polyester fiber

[0108] The spinning raw material polyester is high melt index PBT.

[0109] The high melt index PBT chips were melted in a single screw extruder to obtain a melt, and the melt was spun through a spinneret at 285° C. The filaments were drawn at 65° C. with a drawing ratio of 4.0, and shaped at 150° C. The filaments were cut into 38 mm polyester staple fibers.

[0110] 1.2. Weaving of grey cloth

[0111] The polyester staple fiber of step 1.1 is spun into a 32S / 2 double-ply yarn, and then the double-ply yarn is woven into a yarn with a warp density of 170 strands / 10 cm, a weft density of 126 strands / 10 cm, a width of 160 cm, and a gram weight of 125 g / m 2 Grey cloth.

[0112] 2. Flame retardant treatment

[0113] (i) The grey cloth described in step 1.2 is immersed in a flame retardant treatment liquid for 30 minutes as the object to be flame retardant treated. The immersion temperature is 25°C. The mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.05. The flame retardant treatment liquid is a mixed aqueous solution of methanesulfonic acid and cyclohexanehexol hexaphosphate. The weight content of cyclohexanehexol hexaphosphate in the mixed aqueous solution is 30%, and the weight of methanesulfonic acid is 200 ppmw relative to the weight of cyclohexanehexol hexaphosphate.

[0114] Then the impregnated fiber product is squeezed to obtain the object to be dried (the squeezing times and force are adjusted to control the liquid holding amount of the flame retardant treatment liquid in the object to be dried to be 20%).

[0115] (ii) drying the above-mentioned material to be dried at 150° C. for 10 min to obtain a textile product.

[0116] According to the measurement, the LOI of the fabric product is 23.0%, the breaking strength of the fabric product is 424.5N, and the breaking elongation of the fabric product is 32.7%.

[0117] [Example 1]

[0118] 1. Preparation of primary fiber products

[0119] Preparation of 1.1, 2.22dtex polyester fiber

[0120] The spinning raw material polyester is low melt index PET and high melt index polyester, the high melt index polyester is high melt index PET, and the mass ratio of high melt index polyester to low melt index PET is 0.05.

[0121] Low melt index PET chips and high melt index PET chips are mixed, melted in a single screw extruder to obtain a melt, and the melt is spun through a spinneret at 285° C. The filaments are drawn at 65° C. with a drawing ratio of 4.0, and are shaped at 150° C. The filaments are cut into 38 mm polyester staple fibers.

[0122] 1.2. Weaving of grey cloth

[0123] The polyester staple fiber of step 1.1 is spun into a 32S / 2 double-ply yarn, and then the double-ply yarn is woven into a yarn with a warp density of 170 strands / 10 cm, a weft density of 126 strands / 10 cm, a width of 160 cm, and a gram weight of 125 g / m 2 Grey cloth.

[0124] 2. Flame retardant treatment

[0125] (i) The grey cloth described in step 1.2 is immersed in a flame retardant treatment liquid for 30 minutes as the object to be flame retardant treated. The immersion temperature is 25°C. The mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.05. The flame retardant treatment liquid is a mixed aqueous solution of methanesulfonic acid and cyclohexanehexol hexaphosphate. The weight content of cyclohexanehexol hexaphosphate in the mixed aqueous solution is 30%, and the weight of methanesulfonic acid is 200 ppmw relative to the weight of cyclohexanehexol hexaphosphate.

[0126] Then the impregnated fiber product is squeezed to obtain the object to be dried (the squeezing times and force are adjusted to control the liquid holding amount of the flame retardant treatment liquid in the object to be dried to be 20%).

[0127] (ii) drying the above-mentioned material to be dried at 150° C. for 10 min to obtain a textile product.

[0128] According to the measurement, the LOI of the fabric product is 23.7%, the breaking strength of the fabric product is 412.8N, and the breaking elongation of the fabric product is 31.9%.

[0129] [Example 2]

[0130] 1. Preparation of primary fiber products

[0131] Preparation of 1.1, 2.22dtex polyester fiber

[0132] The spinning raw material polyester is low melt index PET and high melt index polyester, the high melt index polyester is high melt index PTT, and the mass ratio of high melt index polyester to low melt index PET is 0.05.

[0133] Low melt index PET chips and high melt index PTT chips are mixed, melted in a single screw extruder to obtain a melt, and the melt is spun through a spinneret at 285° C. The filaments are drawn at 65° C. with a drawing ratio of 4.0, and are shaped at 150° C. The filaments are cut into 38 mm polyester staple fibers.

[0134] 1.2. Weaving of grey cloth

[0135] The polyester staple fiber of step 1.1 is spun into a 32S / 2 double-ply yarn, and then the double-ply yarn is woven into a yarn with a warp density of 170 strands / 10 cm, a weft density of 126 strands / 10 cm, a width of 160 cm, and a gram weight of 125 g / m 2 Grey cloth.

[0136] 2. Flame retardant treatment

[0137] (i) The grey cloth described in step 1.2 is immersed in a flame retardant treatment liquid for 30 minutes as the object to be flame retardant treated. The immersion temperature is 25°C. The mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.05. The flame retardant treatment liquid is a mixed aqueous solution of methanesulfonic acid and cyclohexanehexol hexaphosphate. The weight content of cyclohexanehexol hexaphosphate in the mixed aqueous solution is 30%, and the weight of methanesulfonic acid is 200 ppmw relative to the weight of cyclohexanehexol hexaphosphate.

[0138] Then the impregnated fiber product is squeezed to obtain the object to be dried (the squeezing times and force are adjusted to control the liquid holding amount of the flame retardant treatment liquid in the object to be dried to be 20%).

[0139] (ii) drying the above-mentioned material to be dried at 150° C. for 10 min to obtain a textile product.

[0140] According to the measurement, the LOI of the fabric product is 24.1%, the breaking strength of the fabric product is 426.0N, and the breaking elongation of the fabric product is 33.3%.

[0141] [Example 3]

[0142] 1. Preparation of primary fiber products

[0143] Preparation of 1.1, 2.22dtex polyester fiber

[0144] The spinning raw material polyester is low melt index PET and high melt index polyester, the high melt index polyester is high melt index PBT, and the mass ratio of high melt index polyester to low melt index PET is 0.05.

[0145] Low melt index PET chips and high melt index PBT chips are mixed, melted in a single screw extruder to obtain a melt, and the melt is spun through a spinneret at 285° C. The filaments are drawn at 65° C. with a drawing ratio of 4.0, and are shaped at 150° C. The filaments are cut into 38 mm polyester staple fibers.

[0146] 1.2. Weaving of grey cloth

[0147] The polyester staple fiber of step 1.1 is spun into a 32S / 2 double-ply yarn, and then the double-ply yarn is woven into a yarn with a warp density of 170 strands / 10 cm, a weft density of 126 strands / 10 cm, a width of 160 cm, and a gram weight of 125 g / m 2 Grey cloth.

[0148] 2. Flame retardant treatment

[0149] (i) The grey cloth described in step 1.2 is immersed in a flame retardant treatment liquid for 30 minutes as the object to be flame retardant treated. The immersion temperature is 25°C. The mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.05. The flame retardant treatment liquid is a mixed aqueous solution of methanesulfonic acid and cyclohexanehexol hexaphosphate. The weight content of cyclohexanehexol hexaphosphate in the mixed aqueous solution is 30%, and the weight of methanesulfonic acid is 200 ppmw relative to the weight of cyclohexanehexol hexaphosphate.

[0150] Then the impregnated fiber product is squeezed to obtain the object to be dried (the squeezing times and force are adjusted to control the liquid holding amount of the flame retardant treatment liquid in the object to be dried to be 20%).

[0151] (ii) drying the above-mentioned material to be dried at 150° C. for 10 min to obtain a textile product.

[0152] According to the measurement, the LOI of the fabric product is 24.5%, the breaking strength of the fabric product is 426.1N, and the breaking elongation of the fabric product is 33.5%.

[0153] [Example 4]

[0154] 1. Preparation of primary fiber products

[0155] Preparation of 1.1, 2.22dtex polyester fiber

[0156] The spinning raw material polyester is low melt index PET and high melt index polyester, the high melt index polyester is high melt index PTT and high melt index PBT, the mass ratio of high melt index polyester to low melt index PET is 0.05, and the mass ratio of high melt index PBT to high melt index PTT is 1.

[0157] Low melt index PET chips, high melt index PTT chips and high melt index PBT chips are mixed and melted in a single screw extruder to obtain a melt, and the melt is spun through a spinneret at 285° C. The filaments are drawn at 65° C. with a drawing ratio of 4.0, and are shaped at 150° C. The filaments are cut into 38 mm polyester staple fibers.

[0158] 1.2. Weaving of grey cloth

[0159] The polyester staple fiber of step 1.1 is spun into a 32S / 2 double-ply yarn, and then the double-ply yarn is woven into a yarn with a warp density of 170 strands / 10 cm, a weft density of 126 strands / 10 cm, a width of 160 cm, and a gram weight of 125 g / m 2 Grey cloth.

[0160] 2. Flame retardant treatment

[0161] (i) The grey cloth described in step 1.2 is immersed in a flame retardant treatment liquid for 30 minutes as the object to be flame retardant treated. The immersion temperature is 25°C. The mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.05. The flame retardant treatment liquid is a mixed aqueous solution of methanesulfonic acid and cyclohexanehexol hexaphosphate. The weight content of cyclohexanehexol hexaphosphate in the mixed aqueous solution is 30%, and the weight of methanesulfonic acid is 200 ppmw relative to the weight of cyclohexanehexol hexaphosphate.

[0162] Then the impregnated fiber product is squeezed to obtain the object to be dried (the squeezing times and force are adjusted to control the liquid holding amount of the flame retardant treatment liquid in the object to be dried to be 20%).

[0163] (ii) drying the above-mentioned material to be dried at 150° C. for 10 min to obtain a textile product.

[0164] According to the measurement, the LOI of the fabric product is 25.1%, the breaking strength of the fabric product is 428.2N, and the breaking elongation of the fabric product is 34.0%.

[0165] [Example 5]

[0166] 1. Preparation of primary fiber products

[0167] Preparation of 1.1, 2.22dtex polyester fiber

[0168] The spinning raw material polyester is low melt index PET and high melt index polyester, the high melt index polyester is high melt index PTT and high melt index PBT, the mass ratio of high melt index polyester to low melt index PET is 0.05, and the mass ratio of high melt index PBT to high melt index PTT is 1.

[0169] Low melt index PET chips, high melt index PTT chips and high melt index PBT chips are mixed and melted in a single screw extruder to obtain a melt, and the melt is spun through a spinneret at 285° C. The filaments are drawn at 65° C. with a drawing ratio of 4.0, and are shaped at 150° C. The filaments are cut into 38 mm polyester staple fibers.

[0170] 1.2. Weaving of grey cloth

[0171] The polyester staple fiber of step 1.1 is spun into a 32S / 2 double-ply yarn, and then the double-ply yarn is woven into a yarn with a warp density of 170 strands / 10 cm, a weft density of 126 strands / 10 cm, a width of 160 cm, and a gram weight of 125 g / m 2 Grey cloth.

[0172] 2. Flame retardant treatment

[0173] 2.1 Alcoholysis

[0174] The grey cloth obtained in step 1.2 is used as the raw material grey cloth and immersed in the alcoholysis treatment solution at 190°C for 50 seconds, then the grey cloth is immediately taken out and immersed in water for 2 times, the immersion temperature is 50°C, each immersion is 30 minutes, and the amount of water used each time is 10 times the weight of the raw material grey cloth; then, the grey cloth is taken out, the flowing water in the grey cloth is squeezed out, and the grey cloth is placed in a blast drying oven at 70°C for 4 hours to obtain an alcoholysis treated fiber product. The mass ratio of the raw material grey cloth to the alcoholysis treatment solution is 0.1, the alcoholysis treatment solution is an alcohol solution of anhydrous zinc acetate, the content of anhydrous zinc acetate relative to alcohol is 100ppmw, and the alcohol is ethylene glycol.

[0175] 2.2 Flame retardant treatment

[0176] (i) The alcoholysis treated fiber product described in step 2.1 is immersed in a flame retardant treatment liquid for 30 minutes as the object to be flame retardant treated. The immersion temperature is 25°C. The mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.05. The flame retardant treatment liquid is a mixed aqueous solution of methanesulfonic acid and cyclohexanehexol hexaphosphate. The weight content of cyclohexanehexol hexaphosphate in the mixed aqueous solution is 30%, and the weight of methanesulfonic acid is 200 ppmw relative to the weight of cyclohexanehexol hexaphosphate.

[0177] Then the impregnated fiber product is squeezed to obtain the object to be dried (the squeezing times and force are adjusted to control the liquid holding amount of the flame retardant treatment liquid in the object to be dried to be 20%).

[0178] (ii) drying the above-mentioned material to be dried at 150° C. for 10 min to obtain a textile product.

[0179] According to the measurement, the LOI of the fabric product is 33.4%, the breaking strength of the fabric product is 428.5N, and the breaking elongation of the fabric product is 34.1%.

[0180] [Example 6]

[0181] 1. Preparation of primary fiber products

[0182] Preparation of 1.1, 2.22dtex polyester fiber

[0183] The spinning raw material polyester is low melt index PET and high melt index polyester, the high melt index polyester is high melt index PTT and high melt index PBT, the mass ratio of high melt index polyester to low melt index PET is 0.05, and the mass ratio of high melt index PBT to high melt index PTT is 1.

[0184] Low melt index PET chips, high melt index PTT chips and high melt index PBT chips are mixed and melted in a single screw extruder to obtain a melt, and the melt is spun through a spinneret at 285° C. The filaments are drawn at 65° C. with a drawing ratio of 4.0, and are shaped at 150° C. The filaments are cut into 38 mm polyester staple fibers.

[0185] 1.2. Weaving of grey cloth

[0186] The polyester staple fiber of step 1.1 is spun into a 32S / 2 double-ply yarn, and then the double-ply yarn is woven into a yarn with a warp density of 170 strands / 10 cm, a weft density of 126 strands / 10 cm, a width of 160 cm, and a gram weight of 125 g / m 2 Grey cloth.

[0187] 2. Flame retardant treatment

[0188] 2.1 Alcoholysis

[0189] The grey cloth obtained in step 1.2 is used as the raw material grey cloth and immersed in the alcoholysis treatment solution at 190°C for 50 seconds, then the grey cloth is immediately taken out and immersed in water for 2 times, the immersion temperature is 50°C, each immersion is 30 minutes, and the amount of water used each time is 10 times the weight of the raw material grey cloth; then, the grey cloth is taken out, the flowing water in the grey cloth is squeezed out, and the grey cloth is placed in a blast drying oven at 70°C for 4 hours to obtain an alcoholysis treated fiber product. The mass ratio of the raw material grey cloth to the alcoholysis treatment solution is 0.1, the alcoholysis treatment solution is an alcohol solution of anhydrous zinc acetate, the content of anhydrous zinc acetate relative to alcohol is 100ppmw, and the alcohol is trimethylolpropane.

[0190] 2.2 Flame retardant treatment

[0191] (i) The alcoholysis treated fiber product described in step 2.1 is immersed in a flame retardant treatment liquid for 30 minutes as the object to be flame retardant treated. The immersion temperature is 25°C. The mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.05. The flame retardant treatment liquid is a mixed aqueous solution of methanesulfonic acid and cyclohexanehexol hexaphosphate. The weight content of cyclohexanehexol hexaphosphate in the mixed aqueous solution is 30%, and the weight of methanesulfonic acid is 200 ppmw relative to the weight of cyclohexanehexol hexaphosphate.

[0192] Then the impregnated fiber product is squeezed to obtain the object to be dried (the squeezing times and force are adjusted to control the liquid holding amount of the flame retardant treatment liquid in the object to be dried to be 20%).

[0193] (ii) drying the above-mentioned material to be dried at 150° C. for 10 min to obtain a textile product.

[0194] According to the measurement, the LOI of the fabric product is 35.0%, the breaking strength of the fabric product is 429.3N, and the breaking elongation of the fabric product is 34.5%.

Claims

1. A method for producing a flame retardant polyester fiber product, comprising the following steps: (1) Mixing and melting low melt index PET chips and high melt index polyester chips to obtain polyester melt. The polyester melt is subjected to spinning, drawing and shaping to obtain primary polyester fibers; (2) In the presence of an esterification reaction catalyst, the primary fiber product as the object to be flame retardant treated is flame retardant treated with a phosphorus-containing compound containing the following structural fragments: ; The high melt index polyester includes high melt index PBT and high melt index PTT; The mass ratio between high melt index PBT and high melt index PTT is 0.1~10; The melt index of the low melt index is a g / 10min, where a is 10 to 30; The melt index of the high melt index polyester is b g / 10 min, b=a+c, c is greater than 0 and less than 90; The test temperature of the melt index is 280° C., and the test load is 2.16 kg.

2. The production method according to claim 1, characterized in that The mass ratio of the high melt index polyester to the low melt index PET is greater than 0 and less than 0.

2.

3. The production method according to claim 2, characterized in that The mass ratio of high melt index polyester to low melt index PET is 0.01~0.

15.

4. The production method according to claim 1, characterized in that The spinning temperature is 260~295℃.

5. The production method according to claim 1, characterized in that The drafting ratio is 3.0~5.

0.

6. The production method according to claim 1, characterized in that The drawing temperature is 60~80℃.

7. The production method according to claim 1, characterized in that The setting temperature is 140~160℃.

8. The production method according to claim 1, characterized in that The phosphorus-containing compound in step (2) includes cyclohexanehexol hexaphosphoric acid.

9. The production method according to claim 1, characterized in that The esterification catalyst is a compound having a sulfonic acid group.

10. The production method according to claim 9, characterized in that The esterification catalyst is methanesulfonic acid, benzenesulfonic acid or p-toluenesulfonic acid.

11. The production method according to claim 1, characterized in that: The flame retardant treatment in step (2) comprises the following steps: (i) impregnating the object to be flame retardant treated with a flame retardant treatment liquid to obtain an object to be dried, wherein the flame retardant treatment liquid contains the above-mentioned phosphorus-containing compound and an esterification reaction catalyst; (ii) Drying.

12. The production method according to claim 11, characterized in that: The solvent of the flame retardant treatment liquid in step (i) is water.

13. The production method according to claim 11, characterized in that: The weight content of the phosphorus-containing compound in the flame retardant treatment liquid in step (i) is 10-40%.

14. The production method according to claim 11, characterized in that: In step (i), the mass ratio of the object to be flame retardant treated to the flame retardant treatment liquid is 0.01-0.

1.

15. The production method according to claim 11, characterized in that: The amount of the esterification catalyst used is 100 to 1000 ppm by weight relative to the phosphorus-containing compound.

16. The production method according to claim 11, characterized in that: The drying temperature in step (ii) is 120-180°C.

17. The production method according to claim 11, characterized in that: The drying time in step (ii) is 3 to 15 minutes.

Citation Information

Patent Citations

  • Method for producing flame-retardant polyester staple fibers by utilizing recovered polyester bottle chips

    CN102102241A

  • A high-strength flame-retardant polyester industrial yarn and its preparation method

    CN110528109B

  • Flame-retardant terylene main yarn and preparation process thereof

    CN112195532A

  • Preparation method of medical gauze with high water absorption and antibacterial activity

    CN113981684A

  • Method for activating surface of polyester fiber

    CN114622402A